PERSEPSI GENERASI MUDA TERHADAP LITERASI KEWARGAAN, NILAI KEMANUSIAAN DAN GLOBAL CITIZENSHIP EDUCATION DI ERA DIGITAL - Kusman Rukmana; Alifa Zahra; Naila Nursifa Rohmah; Indah Zahrotunnisa (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2026)
The rapid development of the digital era requires young people to possess strong civic literacy, humanitarian values, and Global Citizenship Education (GCED) awareness to participate responsibly in society. This study aims to describe young people's perceptions of civic literacy, humanitarian values, and GCED in the digital era. This research employed a descriptive quantitative approach with 46 respondents aged 17–27 years selected through purposive sampling. The instrument used was a closed-ended Likert-scale questionnaire distributed online. Data were collected through an online survey and analyzed using descriptive quantitative analysis. Data validity was ensured through item consistency and researcher reflexivity. The results show that young people generally have positive perceptions of civic literacy, humanitarian values, and GCED; however, a gap remains between awareness and actual participation. This study recommends strengthening digital-based civic education and increasing young people's active social participation.